Label-free voltammetric detection of single-nucleotide mismatches recognized by the protein MutS - Masarík, Michal; Cahová, Katerina; Kizek, Rene; Palecek, Emil; Fojta, Miroslav (Analytical and bioanalytical chemistry, 2007)
MutS, a protein involved in DNA mismatch repair, recognizes mispaired and unpaired bases in duplex DNA. We have previously used MutS in an electrochemical double-surface technique (DST) for in-vitro detection of point mutations in DNA. The DST involved binding of unlabeled MutS to DNA heteroduplexes at the surface of magnetic beads followed by a highly sensitive electrochemical determination of the protein by measurement of a catalytic protein signal (peak H) at mercury electrodes. Detection of MutS using a peak resulting from oxidation of tyrosine and tryptophan residues of the protein at a carbon-paste electrode (CPE) was also possible but was approximately three orders of magnitude less sensitive. In this work we present an optimized technique for ex-situ voltammetric determination of MutS at a CPE. Choice of optimum experimental conditions (pH of supporting electrolyte, square-wave voltammetry settings, etc.) resulted in substantial improvement of the sensitivity of the assay, enabling detection of approximately 140 pg (1.6 fmol protein monomer) MutS in a 5-microL sample. The sensitivity was increased further by acid hydrolysis of the protein before measurement. The hydrolyzed protein was detectable down to 5 pg (approx. 56 amol) MutS in 5 microL solution. By using the DST combined with determination of the bound unlabeled MutS at the CPE we demonstrated selective interactions of the protein with single-base mismatches and discrimination among different base mispairs in 30-mer or 95-mer DNA duplexes. In agreement with previous studies, binding of the protein to the 30-mer substrates followed the trend G:T>>C:A>A:A>C:T>homoduplex. The electrochemical data were confirmed by use of an independent technique-a quartz-crystal microbalance for real-time monitoring of MutS interactions with DNA duplexes containing different base mispairs. By using the electrochemical DST a G:T mismatch was detectable in up to 1000-fold excess of homoduplex DNA.
Keywords: sekvence nukleotidů; Electrodes; uhlík; biosenzitivní techniky; heteroduplexy nukleové kyseliny; molekulární sekvence - údaje; Electrochemistry; Nucleic Acid Heteroduplexes; chybné párování bází; elektrody; Biosensing Techniques; vazebný protein MutS opravné syntézy DNA; elektrochemie; Carbon; Sensitivity and Specificity; senzitivita a specificita; DNA; Molecular Sequence Data; Base Sequence; Base Pair Mismatch; MutS DNA Mismatch-Binding Protein